Supporting and Inhibiting Factors of Character Education in Learning Social Studies at Primary Schools - Hasnah Kanji; Nursalam Nursalam; Muhammad Nawir; Suardi Suardi (Universitas of Muhammadiyah Makassar, 2020)
The main problem of this study is that the students encounter a moral decadence which requires the integration support of character education in learning and anticipates various barriers to the integration of character education in learning. The purpose of this study was to identify various factors supporting and inhibiting character education specifically on social studies learning at primary schools. The research method used descriptive qualitative at SD Inpres 34 Bungung Katammu, Bantaeng Regency. In choosing the research informant,the researcher used purposive sampling, namely the principal, teachers, students and parents. Data collection technique used observation, depth-interview and documentation. Techniques of data analyzis were data reduction, data display and drawing conclusion. The technique of data validity was done through triangulation of sources, time and techniques. Based on the research findingsfrom various researchers, there has been no research which evaluates character education in learning of social study at primary schools which includes input, process and output of learning in high grade. The Factors in supporting and inhibiting character education at SD 34 Bungung Katammung consist of two aspects, namely internal and external. Supporting factors include teachers, principals (internal), parents (external) and inhibiting factors include teachers, principals (internal) and parents (external).Keywords:Integration Mode, Character Education, Learning, Social Studies. Masalah utama dalam penelitian ini adalah kalangan pelajar mengalami dekadensi moral yang membutuhkan dukungan integrasi pendidikan karakter dalam pembelajaran dan mengantisipasi berbagai hambatan integrasi pendidikan karakter dalam pembelajaran. Tujuan penelitian ini untuk mengidentifikasi berbagai faktor pendukung dan penghambat pendidikan karakter terkhsusus pada pembelajaran ilmu pengetahuan social di sekolah dasar. Metode penelitian menggunakan deskriptif kualitatif SD Inpres 34 Bungung Katammu Kabupaten Bantaeng. Penentuan informan penelitian secara purposive sampling, yaitu kepala sekolah, guru, siswa dan orang tua. Teknik pengumpulan data menggunakan observation, depth-Interview dan dokumentasi. Teknik Analisis melalui data reduction, data display dan conclusion drawing. Teknik keabasahan data dilakukan melalui triangulasi sumber, waktu dan teknik. Bedasarkan hasil penelitian dari berbagai peneliti, belum ada penelitian yang melakukan evaluasi pendidikan karakter dalam pembelajaran ilmu pengetahuan sosial di sekolah dasar yang mecakup input, proses dan output pembelajaran di kelas tinggi. Faktor mendukung dan penghambat pendidikan karakter di SD 34 Bungung Katammung terdiri dari dua aspek yaitu internal dan eksternal. Faktor pedukungnya mencakup guru, kepala sekolah (internal), orang tua (eksternal) dan faktor penghambatnya mencakup guru, kepala sekolah (internal) dan orang tua (eksternal).Kata kunci: Model Integrasi, Pendidikan Karakter, Pembelajaran, Ilmu Pengetahuan Sosial.